Individuals, Institutions and Character Development: A Critical Detour through Emerson’s, Nietzsche’s and Foucault’s Ideas (Nóema, 2023)
This article wants to describe in a synthetical way the relationship that bonds the person and the institutions regarding the development of the individual character. This pictures uses Foucault's concepts of subjection, subjectification and resubjectification along his concept of normalization and Emersons' concept of "gleam of light" in Naoko Saito's reading of it. This article follows the following three conceptual steps: first, normalization ad a tool used by institutions to survive and thrive in their status quo; second, "gleam of light" as the chance to emancipate oneself from the dynamics related to normalization; third, the necessity that education reaches a psycagogical dimension in order to avoid that the usage of gleam of light as a leading principle becomes erratic, and it reaches a systematic usage instead.
Keywords: Subjectification; Character Education; Subjugation; Gleam of Light; Naoko Saito; Ralph Waldo Emerson; Friedrich Nietzsche; Psychagogy; Michel Foucault